2014
DOI: 10.18632/oncoscience.33
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of circulating endocannabinoids associated with cancer and metastases in mice and humans

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACT:Background and aims: Endocannabinoids may modify cancer development, progression and associated pain. We determined whether cancer-evoked dysregulations in this system become manifest in altered tissue and plasma endocannabinoids.Methods: Endocannabinoid changes due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 45 publications
7
23
0
Order By: Relevance
“…pathology (Sailler et al, 2014). A similar situation has been proposed for cannabinoid receptors and endocannabinoid degrading enzymes.…”
Section: -Endocannabinoid System: Role In Tumor Generation and Progrmentioning
confidence: 56%
“…pathology (Sailler et al, 2014). A similar situation has been proposed for cannabinoid receptors and endocannabinoid degrading enzymes.…”
Section: -Endocannabinoid System: Role In Tumor Generation and Progrmentioning
confidence: 56%
“…The EC system is involved in many pathophysiological processes, and its role in cancerogenesis has been postulated [33]. The cancer-associated dysregulation of the EC system might lead to measurable changes in circulating EC levels [34]. Here, we investigated the potential role of the EC system as a disease-specific circulating hallmark of rare MPN.…”
Section: Discussionmentioning
confidence: 99%
“…Also the expression of CB 1 and CB 2 receptors was found to increase in mantel cell lymphoma and fatty acid amide hydrolase (FAAH) expression was reduced when compared to non-malignant B-cells (Islam et al, 2003;Ek et al, 2002;Wasik et al, 2014). It has also been shown in both the mouse model of metastatic melanoma and in humans that the circulating endocannabinoid levels have been associated with an increase in disease progression (Sailler et al, 2014). Indeed many reports have shown that an increase in the level of endocannabinoids and their receptors correlates with tumour aggressiveness (Malfitano et al, 2011) and that cannabinoids can inhibit the growth of xenograft tumours Carracedo et al, 2006b;Sanchez et al, 2001a).…”
Section: Anti-tumour Effects Of Cannabinoidsmentioning
confidence: 99%